An Analysis of Teachers’ Perceptions Concerning Issues and Challenges in the Age of Artificial Intelligence at University of Gujrat - Dr. Nishat Zafar; Dr. Saira* (Dialogue Social Science Review (DSSR), 2025)
The rapid integration of Artificial Intelligence (AI) into higher education has transformed teaching, learning, and administrative processes, offering both opportunities and challenges for educators. Understanding teachers’ perceptions is critical to ensuring the effective and ethical adoption of AI technologies in universities. This study explores the perceptions of faculty members at the University of Gujrat regarding the issues and challenges associated with AI in higher education. A descriptive survey design was employed, and data were collected through a structured questionnaire administered to a sample of university teachers across multiple faculties. The analysis focused on identifying concerns related to pedagogical implications, ethical dilemmas, technological readiness, and professional development needs. Findings revealed that while teachers recognized the potential of AI to enhance efficiency, personalize learning, and support research, they also expressed concerns about job security, data privacy, ethical use of algorithms, and lack of adequate institutional support and training. The study concludes that addressing these concerns through targeted training programs, policy frameworks, and infrastructural development is essential to ensure the responsible integration of AI in higher education. The results offer valuable insights for policymakers, university administrators, and teacher educators in navigating the evolving landscape of AI-driven education. Keywords: Artificial Intelligence, teachers’ perceptions, higher education, challenges, University of Gujrat